ANALISIS KEMAMPUAN LITERASI KELAS 1 MI MUHAMMADIYAH 5 SURABAYA MENGGUNAKAN MEDIA GAMBAR - Muhammad â€˜Azmii Fakhruddin; Moh Amin Al Aziz; Dias Frendy Arangga (PROCEEDING UMSURABAYA, 2022)
Literacy is the formation of reading and writing skills that have been carried out since school children. The ability of children in terms of reading because children have a high curiosity to know something. Literacy is more than just reading and writing but includes thinking skills according to stages. The learning process using image media aims to improve literacy skills in 1st grade students of MI Muhammadiyah 5 Surabaya, with image media to make children interested in using media. And can provide broader insights with similar themes. This article aims to describe the use of image media to improve literacy skills in 1st grade students of MI Muhammadiyah 5 Surabaya which is used in data collection in the form of qualitative descriptive. Based on the research, it is shown that the use of image media can improve children's literacy skills in terms of reading and writing.Â Keywords: Image media; Literacy skills